A new method for skin aging evaluation of Chinese women. (29th June 2020) - Ye, Rui; Chang, Wenting; Hu, Jingjing; Qiao, Liyuan; Wang, Qianqian
Abstract: Background: With the development of cosmetic industry in China, an aging evaluation method of Chinese women is in great need. Aims: The aim of this study is to establish a skin aging assessment method using convenient portable machine Antera 3D. Methods: The quantitative approach was developed by capturing 11 areas of the face, and overall, 48 parameters were extracted for aging evaluation. Later, 297 subjects were recruited to take facial image and life style questionnaire. Evaluation of age was accomplished by establishing prediction method with detected skin traits. Results: The age prediction model was built by using the evaluated facial traits, and a R square of 0.6 is achieved by comparing to the chronological age. The crow's feet, cheek skin pigmentation, forehead skin tone, and wrinkles around the month are critical factors in evaluating Chinese women skin aging. In addition, we also explored life styles associated with important skin aging traits. Conclusion: The method developed in this research provides reliable alternative in aging study of Chinese women.